INFLUENCE PERSONAL CHARACTERISTICS, PHYSICAL WORK ENVIRONMENT, RATING AND REWARD SYSTEMS, ON JOB SATISFACTION THROUGH BURNOUT AS INTERVENING VARIABLES - Adia Adi Prabowo (Faculty of Economics and Business, Jenderal Soedirman University, 2022)
The purpose of this study was to examine the effect of personality characteristics, physical work environment, appraisal and rewards systems, on job satisfaction through the burnout variable. This type of research is descriptive quantitative while the sampling in this study used a sample of 90 samples conducted at the Public Accounting Firm (KAP) located in Central Java and Yogyakarta. The data analysis method was carried out using PLS-SEM analysis, testing PLS-SEM analysis through two stages, namely the measurement model (outer model) and structural model (inner model). The results of this study indicate that the hypothesis of Appraisal and Rewards Systems, personality characteristics, physical work environment on burnout has a positive effect, appraisal and rewards systems, burnout, personality characteristics, physical work environment, on job satisfaction has a positive effect, personality characteristics on job satisfaction through burnout variables. Has a positive effect, while the physical work environment and appraisal and rewards systems variables on job satisfaction through the burnout variable have no effect.